Site selection strategy for photovoltaic power plants construction on gangue hills: An integrated method based on GIS and AHP-TOPSIS - Fang Shi; Xiaodan Li; MIngrui Li; Bo Bai (Energy Strategy Reviews)
China's extensive mining history has led to the formation of numerous abandoned mines and coal gangue hills, which pose significant environmental and social challenges. These sites contribute to ecological degradation, environmental pollution, and socio-economic issues such as unemployment and urban decline. Addressing the management and transformation of these mining wastelands is crucial for sustainable development. This study explores the potential of establishing photovoltaic (PV) power plants on gangue hills as a means of environmental rehabilitation and economic revitalization. By integrating Geographic Information Systems (GIS) and the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS), the research develops a site selection model to evaluate suitable areas for PV construction on gangue hills. The model considers multiple factors, including economic, transportation, geographical, environmental, and social impacts, to ensure optimal site selection and sustainable development. The study focuses on Yangquan City, Shanxi Province, a major coal mining region, and identifies 14 gangue hills suitable for PV construction. The results demonstrate that PV projects on gangue hills can achieve dual benefits of ecological restoration and economic efficiency. The research proposes three development strategies: science popularization and entertainment construction, resource reclamation construction, and ecological restoration construction, tailored to different types of gangue hills. This study provides a comprehensive framework for the sustainable utilization of mining wastelands, offering valuable insights for policymakers and stakeholders in the renewable energy sector.